Four-Headed Arrow Shaped Dual Band Perfect Absorbers for Biosensing Applications - Aytaç ONUR; Mustafa TÜRKMEN; Sabri KAYA (International Journal of Applied Methods in Electronics and Computers, 2016)
In this study, a novel perfect absorber (PA) array based on four-headed arrow nanoparticles for biosensing applications in mid-infrared regime is presented. Proposed PA array has a dual-band spectral response, and the locations of resonances can be adjusted by varying the geometrical dimensions of the structure. Nearly unity absorbance is obtained from the PA array for both resonances. Different dielectric spacers (MgF 2 , SiO 2 , and Al 2 O 3 ) are used to investigate the effects of dielectric spacer on the absorbance characteristics of proposed PA array. Absorbance characteristics of PA array are analyzed by using finite difference time domain (FDTD) method. High field enhancement is achieved by the interaction of the sharp corners of arrow nanoparticles. Linear correlation between the resonance frequencies and the refractive index of cladding mediums is determined. Due to the high refractive index sensitivity and near-field enhancement, and nearly unity absorbance, the proposed dual-band PA array with adjustable spectral responses can be useful for biosensing applications in mid-infrared regime.